УЛС ТӨРИЙН НАМЫН ГИШҮҮД, ДЭМЖИГЧДИЙН ОРОН ЗАЙН ТАРХАЛТЫГ СОНГУУЛИЙН ГАЗАРЗҮЙН ҮҮДНЭЭС ТОДОРХОЙЛОХ СУДАЛГАА: /УИХ-ын 2016 оны сонгуулийн 60-р тойргийн жишээн дээр/ - Д.Оюунчимэг; Г.Цогтдэлгэр (Politology, 2023)
Electoral geographic study is evaluates the election result and spatial dependence. Therefore, the election result is described all over the country and region by the cartography approach. The aim of this research is to determine the micro environmental situations and impact factors using the hot-spot analysis. In addition, the size of research area as an electoral district and gathered information from 480 respondents. The respondents were choses by cluster collection approach using questionnaire method and considered the level of collection as 99% probability and respondents as ±6 interval. This research is significant to determine the political attitude of the citizens, the spatial situations of the political parties, define the spatial dependence and evaluate. The spatial situations by studying the political attitude of the citizens using hot-spot analysis. This research work is the basic study which will be carried out at micro level of electoral geographic study.